The By-Band study: gastric bypass or adjustable gastric band surgery to treat morbid obesity: study protocol for a multi-centre randomised controlled trial with an internal pilot phase. - Rogers, C; Welbourn, R; Byrne, J; Donovan, J; Reeves, B; Wordsworth, S; Andrews, R; Thompson, J; Roderick, P; Mahon, D; Noble, H; Kelly, J; et al. (2014)
BACKGROUND: The prevalence of severe and complex obesity is increasing worldwide and surgery may offer an effective and lasting treatment. Laparoscopic adjustable gastric band and Roux-en-Y gastric bypass surgery are the two main surgical procedures performed. DESIGN: This open parallel-group randomised controlled trial will compare the effectiveness, cost-effectiveness and acceptability of gastric band (Band) versus gastric bypass (Bypass) in adults with severe and complex obesity. It has an internal pilot phase (in two centres) with integrated qualitative research to establish effective and optimal methods for recruitment. Adults with a body mass index (BMI) of 40 kg/m2 or more, or a BMI of 35 kg/m2 or more and other co-morbidities will be recruited. At the end of the internal pilot the study will expand into more centres if the pre-set progression criteria of numbers and rates of eligible patients screened and randomised are met and if the expected rates of retention and adherence to treatment allocation are achieved. The trial will test the joint hypotheses that Bypass is non-inferior to Band with respect to more than 50% excess weight loss and that Bypass is superior to Band with respect to health related quality of life (HRQOL, EQ-5D) at three years. Secondary outcomes include other weight loss measures, waist circumference and remission/resolution of co-morbidities; generic and symptom-specific HRQOL; nutritional blood test results; resource use; eating behaviours and adverse events. A core outcome set for reporting the results of obesity surgery will be developed and a systematic review of the evidence for sleeve gastrectomy undertaken to inform the main study design. DISCUSSION: By-Band is the first pragmatic study to compare the two most commonly performed bariatric surgical procedures for severe and complex obesity. The design will enable and empower surgeons to learn to recruit and participate in a randomised study. Early evidence shows that timely recruitment is possible. TRIAL REGISTRATION: Current Controlled Trials ISRCTN00786323.